Role of High-Frequency Oscillation in Locating an Epileptogenic Zone for Radiofrequency Thermocoagulation - Xu, Xin; Yu, Xingguang; Kang, Guixia; Mao, Zhiqi; Cui, Zhiqiang; Pan, Longsheng; Zong, Rui; Tang, Yuan; Wan, Ming; Ling, Zhipei (Frontiers in Human Neuroscience, 2021)
Radiofrequency thermocoagulation (RFTC) has been proposed as a first-line surgical treatment option for patients with drug-resistant focal epilepsy (DRE) that is associated with gray matter nodular heterotopia (GMNH). Excellent results on seizures have been reported following unilateral RFTC performed on ictal high-frequency-discharge, fast-rhythm, and low-voltage initiation areas. Complex cases (GMNH plus other malformations of cortical development) do not have good outcomes with RFTC. Yet, there is little research studying the effect of high-frequency oscillation in locating epileptogenic zones for thermocoagulation on unilateral, DRE with bilateral GMNH. We present a case of DRE with bilateral GMNH, treated using RFTC on unilateral GMNH and the overlying cortex, guided by stereotactic electroencephalogram (SEGG), and followed up for 69 months. Twenty-four-hour EGG recordings, seizure frequency, post-RFTC MRI, and neuropsychological tests were performed once yearly. To date, this patient is seizure-free, the electroencephalogram is normal, neuropsychological problems have not been found, and the trace of RFTC has been clearly identified on MRI. His dosage of antiepileptic medication has, furthermore, been significantly reduced. It is concluded that RFTC on unilateral DRE with bilateral GMNH may achieve good long-term effects, lasting up to, and perhaps longer than, 69 months. Ictal high-frequency oscillation (fast ripple) inside the heterotopia and the overlying cortex may be the key to this successful effect.